Implementation of Marketing Strategies To Increase Interest in Purchasing Products Resulting From Students Business Practices - Ridwan, Muhamad (Dinasti International Journal of Digital Business Management, 2024)
Marketing is the process of providing satisfaction to consumers to gain profits. The two main marketing goals are to attract new consumers by promising superior value and to retain current consumers by providing satisfaction. In business, the existence of a strategy is very important in marketing a product no matter how good the target market segmentation is, and the market position carried out will not work if it is not followed by the right strategy. Strategy is the steps that must be carried out by a company to achieve its goals. Creative Media State Polytechnic students have the obligation to carry out business practices. Interestingly, of the many products that have been successfully created by creative Polymedia students, there are not many that can survive and be sustainable. Therefore, researchers want to try to analyze how marketing strategies are implemented to increase interest in buying products resulting from students' business practices. This type of research is field research using qualitative descriptive methods and also using library research to complete the data. This collection and research was carried out by observation, interviews and documentation. The results of this research are that by implementing the 7P marketing mix marketing strategy, the student team carrying out business practices has succeeded in increasing purchasing interest before and after implementing the 7P marketing mix marketing strategy.